Association among serum uric acid, hyperactivity, impulsivity and dietary components in adults: a cross-sectional study Uric acid, hyperactivity/impulsivity symptoms, and dietary components in adults - Roberto A. Molina-Campuzano; Mariela Bernabe-Garcia; Felipe Vazquez-Estupiñan; Leonel Jaramillo-Villanueva; Maricela Rodriguez-Cruz; Ricardo Saracco-Alvarez; Claudia Sanchez-Sanchez; Israel Moreno-Moreno; Irma S. Y. Corlay-Noriega (PLoS ONE, 2026)
Background A positive association has been reported between elevated serum levels of uric acid (UA) with impulsivity and hyperactivity, behavior in murine models, and human psychopathologies. Still, other factors, such as diet composition, have not been considered. This study aims to determine the association between serum UA, impulsivity/hyperactivity symptoms, and dietary components in adults with psychiatric disorders. Methods A prospective cross-sectional study was conducted on 128 adults who attended a psychiatric service. Fasting serum UA levels were determined by spectrophotometry. Impulsivity and hyperactivity symptoms were evaluated using the Adult ADHD Self-Report Scale (ASRS). Dietary components, including macronutrients, fiber, fructose, added sugar, vitamin C, zinc, copper, n-3 fatty acids, caffeine, and alcohol, were estimated using a 24-hour recall, food models, and nutrition software. Spearman's correlation and general linear models were applied. The last was used to adjust for confounders. Results Serum UA levels were positively correlated to symptoms of hyperactivity/impulsivity and hyperactivity ( Rho = 0.206, p = 0.020; Rho = 0.194, p = 0.028, respectively). Those correlations remained significant after adjusting for confounders. Every 1 mg/dl increase in serum UA levels predicted an elevation of 1.5 points of the hyperactivity/impulsivity symptoms ( p = 0.002; p- model< 0.001) and 1 point of the hyperactivity symptoms ( p = 0.003; p- model < 0.001). Hyperactivity/impulsivity symptoms together and separated were positively correlated with depression ( Rho = 0.470, Rho = 0.389, Rho = 0.485; all p < 0.001, respectively). Serum UA levels negatively correlated with dietary intake of total fiber, vitamin C, and copper but positively with waist circumference ( Rho = −0.297, Rho = −0.185, Rho = −0.212, and Rho = 0.203, all p < 0.05, respectively). Hyperactivity correlated with dietary zinc, while impulsivity correlated with alcohol consumption ( Rho = −0.185 and Rho = 0.195, p < 0.05, respectively). Conclusion The serum UA concentration independently predicts hyperactivity/impulsivity symptoms in adults with psychiatric disorders.